2020
DOI: 10.1002/app.49571
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid hydrogel based on stereocomplex PDLA/PLLA and gelatin for bone regeneration

Abstract: Natural bone is a perfect combination of dense shell cortical bone and porous core spongiosa. Inspired by this gradient structure, we prepared a double‐layered hydrogel with stereocomplex PDLA‐PEG‐PDLA and PLLA‐PEG‐PLLA as the inner porous core and gelatin/nano hydroxyapitite as the outer strengthen shell. Crosslinking of gelatin with natural crosslinker genipin made the shell available for early supporting and the inner physical hydrogel facilitated new bone formation. Successful synthesis of PDLA‐PEG‐PDLA (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The PDLA/PLLA/Gel/nHA/Gen hydrogel exhibited optimal interconnectivity, vast porosity, and adequate size for nutrient delivery. In vitro tests with mouse MC3T3-E1 pre-osteoblast cells showed that PDLA/PLLA/Gel/nHA/Gen hydrogels improved cell adhesion, cell proliferation, and calcium deposition (Wang, et al, 2020).…”
Section: Crosslinking By Stereocomplex Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…The PDLA/PLLA/Gel/nHA/Gen hydrogel exhibited optimal interconnectivity, vast porosity, and adequate size for nutrient delivery. In vitro tests with mouse MC3T3-E1 pre-osteoblast cells showed that PDLA/PLLA/Gel/nHA/Gen hydrogels improved cell adhesion, cell proliferation, and calcium deposition (Wang, et al, 2020).…”
Section: Crosslinking By Stereocomplex Formationmentioning
confidence: 97%
“…A hybrid hydrogel made of PDLA/PLLA with an outer layer of gelatin/nano hydroxyapatite (PDLA/PLLA/Gel/nHA/Gen) was prepared for bone tissue engineering (Wang, et al, 2020). The PDLA/PLLA/Gel/nHA/Gen hydrogel exhibited optimal interconnectivity, vast porosity, and adequate size for nutrient delivery.…”
Section: Crosslinking By Stereocomplex Formationmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] This adaptability and functionality extend to bone repair, where hydrogel's three-dimensional network structure provides mechanical support at defect sites, facilitates cell migration, proliferation, and differentiation, and enables localized delivery of essential nutrients, accelerating tissue regeneration and promoting stem cell differentiation into osteoblasts. [29][30][31][32][33][34] The integration of nanotechnology with hydrogel systems is advancing comprehensive treatment approaches for bone defects. [35][36][37] Furthermore, in myocardial repair, hydrogel offers localized support and restores normal heart rhythm, with specialized designs preventing adverse ventricular expansion post-myocardial infarction and localized drug supply reducing apoptosis and encouraging tissue regeneration.…”
Section: H Sun Laboratory Of Basic Medicinementioning
confidence: 99%
“…For these reasons, several scaffolds have been realized with stiff thermoplastics, above all biocompatible and biodegradable polyesters, such as poly(lactic acid) (PLA) and poly(ε-caprolactone) (PCL) [ 8 ]. These materials have been combined with bioceramics (e.g., tricalcium phosphate, hydroxyapatite) and/or hydrogels (e.g., gelatin, chitosan, alginate, hyaluronic acid) to enhance the scaffold bioactivity through multiple solutions, including surface-modified polymers [ 9 ], embedded particles/nanoparticles [ 10 , 11 ], co-axial fibers [ 12 , 13 ], interpenetrating/semi-interpenetrating networks [ 14 ] and other composite systems [ 15 , 16 , 17 ]. Moreover, tissue regeneration can be promoted by adding cells and growth factors to the scaffolds [ 18 ].…”
Section: Introductionmentioning
confidence: 99%